CROSSED CEREBELLAR DIASCHISIS: A RADIOLOGICAL FINDING IN STATUS EPILEPTICUS NOT TO MISS. Issue 11 (9th October 2013) - Zaidi, Syed
Abstract : Crossed Cerebellar Diaschisis refers to the hypometabolism and loss of functional activity in cerebellar hemisphere contralateral to the supratentorial lesion. It is well recognised following stroke but less commonly reported in patients with status epilepticus. We report a case of status epilepticus with initial MRI findings consistent with Crossed Cerebellar Diaschisis.The abnormalities resolved on successful treatment but subsequently recurred during a second episode of complex partial status epilepticus. We will discuss the images and pathophysiology of crossed Cerebellar diaschisis in status epilepticus.